Physical and mental health among older parents: Does offspring migration and living arrangement matter? Findings from Longitudinal Aging Survey in India (2017-18) - Madhumita Sarkar; Nuruzzaman Kasemi; Malasree Majumder; Md Aslam Sk; Pratik Sarkar; Sourav Chowdhury; Doli Roy; Manik Halder (Elsevier, 2023)
The migration of adult children can have beneficial and adverse effects on the health outcomes of elderly parents left behind. This study examines the effects of adult children's migration on self-rated health and depression among older parents using Longitudinal Ageing Study in India (LASI) 2017-18 with 19,401 individuals aged 60 years or older. Binary logistic regression models were performed to determine the association of self-rated health and depression with adult-child migration status while adjusting for living arrangements and socioeconomic factors. Results show that 36 percent of older parents have at least one migrant child, and 35 percent are empty nesters. Older adults living with their children experience positive impacts on their physical and mental health. Our study reveals that empty-nested elderly have a higher prevalence of poor self-rated health and depression. Irrespective of migrant children, the availability of children in the household matters most regarding parents' health care, as our study suggests no significant difference in physical and mental health among left-behind and non-left-behind older parents. This study aims to draw policymakers' attention to the impact of adult children or youth migration on older parents' physical and mental health. To address this issue, policies should prioritize raising awareness among migrant children of older adults about the importance of maintaining frequent contact and visiting their aging parents.